TEMPORAL ANALYSIS OF MICROWAVE RADIATION EMITTED BY STEPPED LEADERS OF A CLOUD-TO-GROUND FLASH - Baharin, S.A.S.; Ahmad, M.R.; Alkahtani, A.A.; Esa, M.R.M.; Sidik, M.A.B. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Lightning emits electromagnetic waves at various frequency spectrum band. In this paper, we report observational study of microwave radiation emitted by lightning. The lightning measurement is conducted by using an air-gap parallel plate antenna that resonate at around 1 GHz with a bandwidth of 20 MHz. The recorded microwave radiation waveform is analyzed based on the waveform of Fast E-field Antenna (FA). Although the stepped leader (SL) discharge process radiates well at microwave radiation, there is a higher microwave radiation preceded the stepped leader which is identified as Quiet Period, (QP). The average duration of QP is 3.707 µs while the average duration of SLs recorded is 2.883 µs. The percentage ratio of the peak amplitudes of the microwave bursts during QP is between 34.3% and 49.5% larger than the amplitude of the microwave bursts during SLs. Microwave radiation is seen to initiate the stepped leader process as the largest amplitudes of microwave burst is recorded during the QP. The characteristics of the microwave waveforms of SL and QP are observed to be oscillating individual pulses but the peak amplitudes of the microwave radiation bursts during the QP are larger than during SLs.